Gardening for food and fun ([Washington, D.C.] : U.S. Dept. of Agriculture : For sale by the Supt. of Docs., U.S. G.P.O., 1977)
A practical book for gardeners of all types that tells how to preserve and store your gardens produce at peak quality for year-round use, and it stresses the need for proper techniques to avoid health hazards
Includes index
Includes bibliographies pp. 385-386
eej 15/01/2019
Loans
Keywords: Vegetable gardening; Fruit-culture.; Food